The taxonomic identity of Trigona lacteipennis Friese, 1900 and description of a new bee species of the Trigona cilipes (Fabricius, 1804) group (Hymenoptera: Apidae: Meliponini) - Oliveira, Favízia Freitas De; Engel, Michael S.; Rasmussen, Claus; Ribeiro, Cristiano Feitosa; Urban, Danúncia (Zootaxa, 2024)
A critical study of type material for Trigona lacteipennis Friese, 1900 and allied species is presented along with a discussion of literature data. This work reveals that T. lacteipennis is a junior subjective synonym of Melipona paupera Provancher, 1889 (new synonymy), a species currently classified placed in the genus Frieseomelitta. Similarly, T. lehmanni Friese, 1901 and T. parastigma Cockerell, 1918 are also junior subjective synonyms of Melipona paupera (new synonymies). Morphological characters, photographic illustrations of type specimens, and data on distribution are provided for Frieseomelitta paupera. Also, we describe a new species of Trigona cilipes species group, Trigona (Aphaneuropsis) silveirai sp. nov., which is very similar to the former and had been misidentified with it.